Shortage of Technicians, Intellectual Property Rights Disputes and Labor Property Rights - Dai, Jingchao; Wang, Lucong (International Journal of Emerging Trends in Social Sciences, 2019)
This paper analyzes the shortage of technical personnel in China from the perspective of intellectual property rights (IPR) protection and the labor property rights. From the micro point of view, this paper points out that due to the uniqueness of intellectual labor, intellectual property right system and the incomplete property rights of intellectual labor, intellectual property rights disputes occur between technical personnel and enterprises. Such conflicts greatly reduce the return on human capital investment of skilled personnel, which leads to insufficient supply of labor and shortage of skilled workers. This paper also puts forward how to alleviate and avoid the disputes of intellectual property rights and the shortage of technical personnel.